In the Shadow of the Razor Wire: Class and Insecurity in Guatemala’s Urban Core - Torres, M. Gabriela (Anthropologica, 2015)
Entering the global search for an ever-elusive sense of security, Guatemalan homes are adorned with razor wiring. Modern security paraphernalia today build on the long-standing socially accepted paranoia about outsiders disrupting the sanctity of the home. The country’s history of inter-ethnic inequality and political violence now reinforces a particular architectural aesthetic that symbolizes the ways that relationships with out siders are understood. Yet residential spaces in the city core are not solely a product of underlying cultural and historical influences but also reflect more recent market-oriented neoliberal patterns of consumption and citizenship.